Implementasi Sistem Informasi Berbasis Web Pada Pengelolaan Arsip Bagian Sertifikasi Balai BPOM Pekanbaru - Sukrianto, Darmanta; Oktarina, Dwi (Computer Science and Information Technology, 2025)
Archives play a crucial role in the administrative and management activities of an organization as they contain information about daily operations. The BBPOM (Food and Drug Supervisory Agency) in Pekanbaru is a technical unit responsible for overseeing food and drug products in accordance with legal regulations. One of the divisions at BBPOM Pekanbaru is the Certification Division, which is tasked with evaluating the production facilities of food and drug products. Currently, the Certification Division still uses a simple archiving management system, where all physical documents are scanned and stored in Google Drive, while the physical documents are kept in filing cabinets. Although the arrangement is neat, there is still a higher risk of data damage or loss, and it also requires a large storage space. Developing an information system for efficient archiving takes time, but by using the Rapid Application Development (RAD) method, the system can be completed quickly. This web-based archiving information system is designed to make data searches faster by using a search feature for finding document numbers, names, and types. The system also facilitates monitoring of storage spaces and maintaining archived documents, while minimizing the risk of document damage or loss, as access to the archiving system requires a username and password for login.